(untitled) - Ebenhack, Ben W. (Tulsa, Oklahoma 74101)
Energy Resources sets the standard as the most comprehensive investigation about how we acquire and use the natural resources that power our modern world. Coal, petroleum, methane, uranium, biomass, water, wind, geothermal and sunlight are all considered in a deliberate and highly accessible chapter-by-chapter examination.
Keywords: Energy development,Phát triển năng lượng; Enviromental aspects,Khía cạnh môi trường